LEARNING BASED OCEANOGRAPHY LITERACY TO SEE THE RELATIONSHIP BETWEEN KNOWLEDGE COMPETENCIES AND ATTITUDES TO CARE FOR THE MARINE ENVIRONMENT - Siti Nurul Hidayati; Millah Khoirul Muazzah; Hasan Subekti (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2022)
Nowadays, marine environmental problems are already very worrying. Human activity is the main cause of lack of an attitude towards the environment. The research that has been carried out aims to describe the relationship between knowledge and attitudes towards caring for the marine environment that students have, after oceanographic literacy-based learning. The subjects in this study were 30 students in class VII in the area near Paciran beach. Data collection for students' knowledge uses the assignment assessment of poster making and uses questionnaire sheets for student attitudes. Based on the results of the study, 9 data students got poster scores in the very good knowledge category with a very strong attitude category, 13 students in the good knowledge category with 12 students had a very strong attitude category, and one person categorized as a strong attitude, 6 students in the category enough knowledge with very strong attitude categories, the remaining 2 students with less knowledge categories get very strong attitude categories and one of them is strong. Based on calculation using SPSS with a score of 0.695 is known a positive correlation the ability of knowledge and attitudes to care for the environment which is included in the strong category.